Pre-extension demonstration of bread wheat (Triticum aestivum. L) varieties at midlands of Guji zone, Southern Oromia, Ethiopia - Dembi Korji Basha Kebede; Tekle Bobo (Open Journal of Plant Science - Peertechz Publications, 2023)
In Ethiopia, wheat is a strategic crop to solve food insecurity. However, there is a lack of improved variety which can increase surplus production. Thus, demonstration and use of improved and new variety are important for producers. This demonstration aimed to evaluate the yield performance and profitability of the Adola 1 bread wheat variety. Adola 1 and the local variety were demonstrated on 10 m x 10 m during the 2021 production year in the midland districts of the Guji zone. Farmers were trained in wheat production. Interviews and measurements were taken to collect the data. The collected data were analyzed by descriptive, net income, and narrations. The result of the demonstration showed that Adola 1 variety gave a higher yield (36.41 qt/ha) than the local variety (23.21 qt/ha) in the Wadera district. The result of net income showed that Adola 1 variety gave more Net income (73266.79 ETB/ha) than the local variety (26830.71 ETB/ha). Production of the Adola 1 variety was more profitable than locally used varieties at Midland. The color of Adola 1 was preferred by farmers for market and household consumption purposes. Adola 1 was an early matured variety so it was preferred by farmers. Adola 1 was more easily threshed than the local variety in the Wadera district. Despite being affected by birds the early maturity of the Adola 1 variety was likened by experimental farmers. Farmers should use Adola 1 variety in their bread wheat production. For further promotion, the pre-scaling up of the Adola 1 variety should be conducted in the midland districts of the Guji zone.